Hygrothermal durability of bond in FRP-strengthened masonry - Ghiassi, Bahman (2014)
Fiber reinforced polymers (FRPs) are accepted as an efficient material for external strengthening of masonry structures. Previous researches have shown that the bond between FRP and the substrate plays an important role in the effectiveness of this strengthening technique. Extensive investigations have been devoted to the characterization of the short-term bond behavior, while its durability and long-term performance requires further studies. In this regard, a full experimental program for investigating the environmental durability of bond in FRP-strengthened masonry is crucial for understanding the degrading mechanisms. This paper presents the results of an experimental program aimed at investigating the hygrothermal durability of bond in FRP-strengthened bricks. Accelerated ageing tests were performed on the FRP-strengthened brick elements and the bond degradation was periodically investigated by visual inspection and by conventional single-lap shear bond tests. The changes in the properties of material constituents have also been monitored. The obtained results are presented and critically discussed.